Effective Parameters in Computational Fluid Dynamics Simulation of Baffled Stirred Column Reactor Hydrodynamics with Sliding Mesh - RAHIMI, R.; ZIVDAR, M.; SALEHI, M.A.; SHAHRAKI, F.; GHANNADZADEH, H. (Asian Journal of Chemistry, 2010)
The main objective of this research is to investigate a mathematical model for use in simulations of baffled stirred reactor hydrodynamics. To evaluate this model, simulations are done for a single-phase impeller stirred vessel in the laboratory. These results are then compared with experimental data from literature. For the single phase system, two different turbulence models were tested. It is clear that the modified model of Chen and Kim for impeller stirred systems is far superior to the standard model used for bubble stirred systems. Also a comparison of sliding mesh, snapshot and empirical source models for impellers are done for the same system. It is shown that the sliding mesh model and the snapshot model give similar results, which may be a small preference for the sliding mesh model. The empirical source model is believed to give good results on time average.